Embedding Strategy in La femme au miroir by Eric-Emmanuel Schmitt - Benyamina, Kaouter (Journal of Human Sciences, 2022)
To understand the art discursive of an author, you should be deep-into his literary universe. The novel entitled La femme au miroir by Eric-Emmanuel Schmitt allowed the identification of a complex structure prompting an investigation of meaning. Thus, the decryption of a nested writing highlights the mechanisms of the embedding. In this sense, three women cohabit in the space of the novel and punctuate the narration in a random manner. From Bruges to Vienna and from Vienna to Hollywood we discover the crossed fate of Anne, Hanna and Anny with three stories, through three different important periods of history, namely: the XVIth century, the XXth and the XXIst century in order to contemplate the reflection of the woman who is seen through time.